Analisis Pola Penempatan Bangunan Perkantoran Kota Tambang Pada Masa Kolonial: Studi Kasus Kota Sawahlunto - Amril, Fazhuni (Jambura History and Culture Journal, 2023)
This study examines the strategic patterns of office building placement in the Colonial Mining Town of Sawahlunto during the Dutch East Indies era, aiming to uncover the underlying strategies and factors influencing location decisions. Employing a qualitative approach grounded in archival historical analysis and primary documentation, the research identifies key geographic, social, and functional considerations that shaped the spatial organization of the town's administrative and economic infrastructure. The analysis reveals a deliberate strategy in placing significant buildings such as the PT BA UPO Headquarters and the Ombilin Cooperative Building in proximity to mining shafts and colonial markets, facilitating efficient administrative and economic coordination. Furthermore, the decision to locate these structures near major transportation routes underscores a commitment to ensuring optimal accessibility within the economic context of a burgeoning mining community. These placement patterns not only reflect adaptations to the geographical and socio-economic conditions prevalent at the time but also highlight a calculated approach to maximizing operational efficiency and economic activities within the town. The implications of this research extend to the fields of landscape archaeology and sustainable development planning, emphasizing the critical importance of integrating historical insights into contemporary urban development strategies. By understanding how historical urban planners navigated similar challenges, contemporary policymakers can derive valuable lessons for addressing current urban development challenges in a sustainable manner. Ultimately, this study contributes to a deeper understanding of historical urban development strategies in colonial contexts, illustrating how human adaptation to local environments and technological contexts has shaped urban landscapes over time